Historical Advancements and Evolution in Understanding Human Anatomy and Pathology: The Contribution of the Middle Ages. (18th May 2021) - Roguin, Alon L.; Roguin, Ariel; Roguin, Nathan
Abstract : Dissections and autopsies are critical for understanding human anatomy, pathology, and uncovering mechanisms of disease. This review presents an historical journey from ancient times until the late Middle Ages. The major steps and developments are summarized with key figures and events presented.